Analysis of a swimmer's hand and forearm in impulsive start from rest using computational fluid dynamics in unsteady flow conditions. (23rd January 2018) - Samson, M.; Monnet, T.; Bernard, A.; Lacouture, P.; David, L.
Abstract: The propulsive forces generated by the hands and arms of swimmers have so far been determined essentially by quasi-steady approaches. This study aims to quantify the temporal dependence of the hydrodynamic forces for a simple translation movement: an impulsive start from rest. The study, carried out in unsteady numerical simulation, couples the calculation of the lift and the drag on an expert swimmer hand-forearm model with visualizations of the flow and flow vortex structure analysis. The results of these simulations show that the hand and forearm hydrodynamic forces should be studied from an unsteady approach because the quasi-steady model is inadequate. It also appears that the delayed stall effect generates higher circulatory forces during a short translation at high angle of attack than forces calculated under steady state conditions. During this phase the hand force coefficients are approximately twice as large as those of the forearm. The total force coefficients are highest for angles of attack between 40° and 60°. For the same angle of attack, the forces produced when the leading edge is the thumb side are slightly greater than those produced when the leading edge is the little finger side.